Developing written translation skills of translation students through a synergetic approach - Fakhodova, Dilnoza (The Lingua Spectrum, 2025)
This article provides a thorough analysis of the theoretical and practical significance of the synergetic approach in developing the written translation skills of students studying translation. The theory of synergetics, which is based on the principles of self- organization in complex systems, can be effectively applied to language learning and, in particular, to the process of translation. Written translation is a complex, multifaceted, and creative activity in which linguistic elements, context, cultural differences, authorial intent, and the needs of the target audience are harmonized within a single integrated system. The article demonstrates how, through the synergetic approach, students can develop comprehensive translation competence by integrating and balancing these interacting components. Additionally, the study presents practical results from an experiment, methodological recommendations for lessons, and an analysis of students’ reflective practices. The findings confirm that the synergetic approach serves as an effective and innovative model for translation education.